Суспільно-правова адаптація осіб, звільнених з місць позбавлення волі під час війни - Романова, Альона; Romanova, Alona (Видавництво Львівської політехніки, 2022)
З’ясовано, що для адаптації осіб звільнених з місць позбавлення волі у правовому просторі держави необхідно забезпечити юридичні консультації особам, що тільки готуються до звільнення, надати їм інформацію для розуміння тієї суспільно-правової ситуації, що є на даний час в країні, адже, такі особи і так «відірвані» від динамічних реалій сучасного життя, а за умов війни, можуть втратити правомірні, ціннісні вектори орієнтації і поведінки в соціумі. Наголошено, що проблемним аспектом дослідження суспільно-правової адаптації осіб звільнених з місць позбавлення волі під час війни є морально-психологічні особливості сприйняття суспільством таких осіб і небажання сприяти їх ресоціалізації, що може провокувати рецидиви неправомірної поведінки і порушення законів. Доведено, що під час військового стану важливим моментом є можливість або її відсутність у звільненого звернутися до державних органів і служб з питань поновлення документів, працевлаштування тощо під час війни. Особливо, коли зруйновані установи, тимчасово окуповані території. Звичайно, можна зустріти недоброчесних громадян, котрі хочуть скористатися таким станом звільненого і тут можливі різні протиправні схеми і діяння з їх сторони: трудове рабство, шахрайські дії щодо майна і житла тощо. Зазначено, що в кризовий період війни первинний і один з найважливіших аспектів соціально-правової адаптації покладається на адміністрації виконання покарань. Засуджені повинні бути максимально підготовлені до того, що вони опиняться у суспільстві, котре жертвує найціннішим заради перемоги у цій жорстокій війні. Тому, значно акцентується роль психологічних служб у місцях позбавлення волі. Акцентовано увагу на проблемі упередженого ставлення працедавців до осіб звільнених з місць позбавлення волі, а під час війни, коли значна кількість громадян втратили постійне місце праці і доходи така ситуація погіршується. Тому, якщо перед звільненням уповноважені органи зможуть розв’язати проблему працевлаштування особи за вказаним напрямом, то одночасно вирішиться ряд проблем соціальних гарантій, які отримують колишні засуджені при працевлаштуванні.

It was found that an important point is the adaptation of persons released from prisons in the legal space of the state. It is necessary to provide legal consultations to persons who are just preparing for release, to provide them with information to understand the social and legal situation that currently exists in the country, because such persons are already «detached» from the dynamic realities of modern life, and under conditions of war , may lose legitimate, valuable vectors of orientation and behavior in society. It is emphasized that a problematic aspect of the study of social and legal adaptation of persons released from prisons during the war is the moral and psychological peculiarities of society's perception of such persons and unwillingness to contribute to their resocialization, which can provoke relapses of illegal behavior and violations of laws. It has been proven that during martial law, an important moment is the possibility or lack of it for a demobilized person to apply to state bodies and services for the renewal of documents, employment, etc. during the war. Especially when institutions are destroyed, temporarily occupied territories. Of course, you can meet unscrupulous citizens who want to take advantage of such a state of release, and various illegal schemes and actions on their part are possible here: labor slavery, fraudulent actions regarding property and housing, etc. It is noted that in the crisis period of the war, the primary and one of the most important aspects of socio-legal adaptation is entrusted to the administration of execution of punishments. Convicts must be prepared as much as possible for the fact that they will find themselves in a society that sacrifices the most valuable for the sake of victory in this cruel war. Therefore, the role of psychological services in places of deprivation of liberty is greatly emphasized. Attention is focused on the problem of prejudiced attitude of employers towards persons released from places of deprivation of liberty, and during the war, when a significant number of citizens lost their permanent place of work and income, this situation worsens. Therefore, if before release, the authorized bodies can solve the problem of employment of a person in the specified direction, then a number of problems of social guarantees, which former convicts receive upon employment, will be solved at the same time.
Socio-legal adaptation of persons persons released from places of deprivation of liberty during the war
Keywords: воєнний стан; соціальна адаптація; соціальний патронаж; органи пробації; особи звільнені з місць позбавлення волі; martial law; social adaptation; social patronage; probation authorities; persons released from prisons; 340.12